Yefimov Yu.V. “Accountability paradox” as factor of public administration system development - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
For the  rst time in the domestic science of public administration a detailed analysis of the “accountability paradox” was conducted, which is to determine the nature of the impact of control activities on the public sector performance. The discussion in the Western science of public administration about the measures aimed at overcoming this paradox is analyzed.